Antimicrobial Resistance Profile and ExPEC Virulence Potential in Commensal Escherichia coli of Multiple Sources - Elisa Massella; Federica Giacometti; Paolo Bonilauri; Cameron J. Reid; Steven P. Djordjevic; Giuseppe Merialdi; C. Bacci; Laura Fiorentini; Paola Massi; Lia Bardasi; Silva Rubini; Federica Savini; et al. (2021)
We recently described the genetic antimicrobial resistance and virulence profile of a collection of 279 commensal E. coli of food-producing animal (FPA), pet, wildlife and human origin. Phenotypic antimicrobial resistance (AMR) and the role of commensal E. coli as reservoir of extra-intestinal pathogenic Escherichia coli (ExPEC) virulence-associated genes (VAGs) or as potential ExPEC pathogens were evaluated. The most common phenotypic resistance was to tetracycline (76/279, 27.24%), sulfamethoxazole/trimethoprim (73/279, 26.16%), streptomycin and sulfisoxazole (71/279, 25.45% both) among the overall collection. Poultry and rabbit were the sources mostly associated to AMR, with a significant resistance rate (p > 0.01) to quinolones, streptomycin, sulphonamides, tetracycline and, only for poultry, to ampicillin and chloramphenicol. Finally, rabbit was the source mostly associated to colistin resistance. Different pandemic (ST69/69*, ST95, ST131) and emerging (ST10/ST10*, ST23, ST58, ST117, ST405, ST648) ExPEC sequence types (STs) were identified among the collection, especially in poultry source. Both ST groups carried high number of ExPEC VAGs (pandemic ExPEC STs, mean = 8.92; emerging ExPEC STs, mean = 6.43) and showed phenotypic resistance to different antimicrobials (pandemic ExPEC STs, mean = 2.23; emerging ExPEC STs, mean = 2.43), suggesting their role as potential ExPEC pathogens. Variable phenotypic resistance and ExPEC VAG distribution was also observed in uncommon ExPEC lineages, suggesting commensal flora as a potential reservoir of virulence (mean = 3.80) and antimicrobial resistance (mean = 1.69) determinants.